MANAJEMEN PROGRAM AKSELERASI DI SMP PL DOMENICO SAVIO SEMARANG - Justina Endang Kartini; Bambang Ismanto (Kelola: Jurnal Manajemen Pendidikan, 2015)
This study aimed to describe the management acceleration program in terms of planning, organizing, actuating, and monitoring learning in PL Domenico Savio Junior High School. This research is a qualitative descriptive study. Subjects were principal, manager acceleration, acceleration secretary, and homeroom teacher. Results of research: Planning accelerated program in PL Domenico Savio Junior High School done by preparing teachers, finance, infrastructure, learners, curriculum, time, and high school. Learning plan covering the syllabus and lesson plan contains learning objectives, teaching materials, teaching methods, learning resources, and assessment of learning outcomes. Organization of human resources contained in the organizational structure of the school is equipped manager acceleration. Organizing accelerated learning includes the step before learning, implementation, and after learning. Teachers organize learning materials to learners’ learning time. Acceleration managers manage learning activities acceleration in school and outside of school. Actuating of accelerated program refers to the RPP and half of each subject program. Implementation of the learning stages: introduction, core activities, and cover. Monitoring the acceleration of learning is done directly by the students, parents of students, and managers acceleration. Learners and parents provide input on school. Manager acceleration control feasibility study. Principal using monitoring results into training materials for teachers. Accelerated learning assessment carried out by the teacher. Teacher evaluations are conducted by the principal and foundations. Reporting accelerated learning is done on the parents of learners.